ENHANCING SPEAKING SKILL THROUGH SPINNING WHEEL MEDIA OF STUDENTS MAJORING IN TRAVEL MANAGEMENT AT TRIATMA MULYA UNIVERSITY - Purwaningsih, Ni Komang; Dewi, Si Putu Agung Ayu Pertiwi (Program Studi Pendidikan Bahasa Indonesia dan Daerah Universitas PGRI Mahadewa Indonesia, 2024)
Speaking skills, especially in presenting something like destinations, attractions and etc are critical for students to comprehend, particularly those majoring in travel management. Communication is deemed good when a tour guide can convey information or facts about a location or anything to guests in a clear and efficient manner. Several strategies are used to develop the speaking abilities of travel management students, one of them is by using a spinning wheel media which consists of several questions which are then answered by the students within a predetermined amount of time. This study investigated the efficacy of employing a spinning wheel media to improve the speaking abilities of students majoring in travel management and also to address the demand for practical and engaging speaking activities suited to the unique context of travel management students. A mixed-methods approach was used, with pre and posttest evaluations, observations, and students’ feedback. Overall, the findings indicated that implementing creative and interactive speaking exercises, such as the spinning wheel media, can considerably improve speaking skills among travel management students which was demonstrated by an increase in students’ pretest scores from 67.25% to 84.75% at the post test. Similarly, students claimed that they were more passionate about learning through this media since they were more pushed and challenged to be able to talk more about the topics they had learned. Further research is needed to determine the long-term impacts and potential applicability of this strategy in other educational settings. Keywords: speaking, presentation, spinning wheel, travel agent